The response of glyphosate-resistant and glyphosate-susceptible biotypes of junglerice (Echinochloa colona) to mungbean interference. Issue 4 (July 2019) - Mutti, Navneet Kaur; Mahajan, Gulshan; Jha, Prashant; Chauhan, Bhagirath S.
Abstract: Glyphosate-resistant junglerice [ Echinochloa colona (L.) Link] is a problematic weed in mungbean [ Vigna radiata (L.) R. Wilczek] crops in Australia. Due to limited herbicide options in mungbean, there is an increased interest in developing integrated management strategies for the sustainable control of E. colona . Pot experiments were conducted in a screenhouse in 2017 and 2018 by growing E. colona plants (glyphosate-resistant [GR] and glyphosate-susceptible [GS] biotypes) alone (1 plant pot −1 ) and in competition with 4 and 8 mungbean plants pot −1 . Both biotypes were developed from a single population using the clone method. The growth and seed production of both GR and GS biotypes were similar in response to mungbean competition. Averaged over biotypes, there was a reduction in the growth and seed production of E. colona as crop plants increased. Compared with the weed plants grown alone, crop interference reduced E. colona height by 17% to 19%, tiller numbers by 69% to 82%, total shoot biomass by 85% to 91%, and inflorescence numbers by 74% to 91%. When E. colona was grown with 8 mungbean plants pot −1, leaf weight ratio increased by 42% compared with plants grown alone. Compared with weed plants grown alone, mungbean interference (4 and 8 plants pot −1 ) reduced weed seed production by 85% to 95%. These reductions were similar for both biotypes (GR and GS), suggesting that there was no fitness penalty associated with resistance. The results of this study suggest that mungbean interference can reduce E. colona growth and seed production, but it should not be considered as a stand-alone strategy to manage E. colona and similar species in mungbean. These results also highlight the need for integrating crop competition with other management strategies to achieve complete and sustainable management of this weed.